Proses Pembuatan Rencana Strategis Badan Pendidikan dan Pelatihan Provinsi DKI Jakarta Dalam Pengembangan Sumber Daya Manusia Aparatur Tahun 2013 - Wicaksono, Muhammad Isaldi; Setiyono, Budi; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
Strategic Plan is a planning document which act as a guideline in achieving the long-term purpose of an organization. The issue raised in this research is: How is the process in formulating strategic plan? How is the process in the establishment of budget plan? What obstacles and issue faced in the process of formulating strategic plan?The aim of this research is to understand the process in formulating strategic plan and to understand the estbalishment of budget planning. Further, this research is also conducted to identify the obstacles and issues faced by Education and Training Agency of Jakarta Capital City [â€œBadan Pendidikan dan Pelatihan Provinsi DKI Jakartaâ€] in formulating a strategic plan.This research is descriptive research using qualitative approach. The informant in this research is the leader and staff of Education and Training Agency of DKI Jakarta Province. This research uses two techniques in collecting data that is in-depth interview and documentation study.In answering such problem and aim of the research theory of strategic planning as one of the formal process in aiding organization in maintaining its optimal position which involves essential elements in such environment is used. Theory of budgetting is also used as an integral part in the process of strategic planning. The object of this research is Education and Training Agency of Jakarta Capital City in 2013.The result of this research shows that Education and Training Agency of DKI Jakarta is successful in producing strategic planning documents correctly because it has fulfilled all aspect in the process of formulating a strategic plan. In regards to estbalishment of budget, no issue were identified since such program and such activity is in accordance with strategic planning. However, the issue faced in the process of formulating strategic plan is the quantity and the quality of human resource.